Beyond Boundaries: Counterculture in Harper Lee’s To Kill A Mockingbird - Panta, Shiva Raj (Bagiswori Journal, 2025)
This research article examines the birth of new cultural practices owing to individual and group inclinations in a literary text To Kill a Mockingbird (1960) by an American writer Harper Lee. This text offers a textual situation that contains a debate around the appropriate and inappropriate attires from the cultural viewpoints. Employing the transcultural theory propounded by Wolfgang Welsch, particularly, the concept of untenable cultural delimitation, the researcher has selected the narrative pieces of the novel in which the clothing behavior of a group or individuals is significantly discussed. Afterwards, the codes, categories and themes are developed for the generation of the analytical framework. Certain individuals and groups who went against the dominant culture were brought together for drawing the conclusion. Two themed analytical framework consisting of individual characters and group scenario is analyzed dominantly through the within case analysis method. Each case is analyzed without much comparison to another case because the case is rich and detailed in itself. This yields the result that a culture cannot accommodate all the interests, inclinations and preferences of an individual or group. The characters go beyond boundaries forming the counterculture. Hence, the study brings the conception to the light that a fictional text includes characters who contribute to the formation of a counterculture. The novelty of the research can be claimed that no research hitherto has studied the attires in the novel to prove the challenge to the cultural delimitation.